If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
6-(2*x) = 6*x-((10*x)/14) // - 6*x-((10*x)/14)
(10*x)/14-(2*x)-(6*x)+6 = 0
(10*x)/14-2*x-6*x+6 = 0
6-51/7*x = 0 // - 6
-51/7*x = -6 // : -51/7
x = -6/(-51/7)
x = 14/17
x = 14/17
| 3v+2v-3v=12 | | 25(z+750)=-575 | | 11/12-1q/6q-1/3 | | 71-x=85-2x | | 20v-19v=13 | | log(x^2+8)=-2 | | 2ln(2)-ln(1)= | | 3f-2f+f=0 | | 756=21(v+10) | | 10t-t=18 | | 73-2x=83-3x | | 67-x=78-2x | | 7b+23=-47 | | 5y-2[3/2y-5] | | 7c-33=58 | | 3x-3(7x+11)=-153 | | w/8-2=1 | | 66-2x=82-3x | | 9f-(-28)=91 | | 6x+x=2(1+3x)-2(1-x) | | 10g-g=9 | | 8=20-2n | | 4(9+3x)-12=6 | | 4x+1x+4=8x-3x+4 | | X+6+7-5=18+4 | | -14=h+7 | | 5(t-87)=10 | | -5(c-89)=-30 | | 13.7b-3=3.43b | | 74-2x=89-3x | | 13.7b-3=3-43b | | 48=12xn |